The Effect of Argument Mapping Supported with Peer Feedback on Pre-Service Teachers' Argumentation Skills. Issue 1 (12th November 2020) - Uçar, Beyza; Demiraslan Çevik, Yasemin
Abstract: This study aims to explore the effect of argument maps supported with peer feedback on pre-service teachers' argumentation skills. The participants consisted of 43 (21 female, 22 male) pre-service teachers studying at the Department of Computer Education and Instructional Technologies. There were two groups as experiment (n = 23) and control (20) in the research. The learners in the control condition developed arguments individually about teaching methods through argument maps. Similar to the control group, those in the experimental condition first accomplished the argument mapping tasks. Later, they performed peer feedback activity. Both quantitative and qualitative analyzes were conducted to gain a deep insight into the effect of these interventions on pre-service teachers' argumentation skills. The results showed that both control and experimental groups' argumentation skills improved statistically significant. Additionally, we found using argument maps with peer feedback gives more positive results compared to the only argument mapping.